Polyunsaturated fatty acids changes during electroconvulsive therapy in major depressive disorder. (April 2023) - van Verseveld, M.; Mocking, R.J.T.; Scheepens, D.; ten Doesschate, F.; Westra, M.; Schoevers, R.A.; Schene, A.H.; van Wingen, G.A.; van Waarde, J.A.; Ruhé, H.G.
Abstract: Polyunsaturated fatty acids (PUFAs) have important electrochemical properties and have been implicated in the pathophysiology of major depressive disorder (MDD) and its treatment. However, the relation of PUFAs with electroconvulsive therapy (ECT) has never been investigated. Therefore, we aimed to explore the associations between PUFA concentrations and response to ECT in patients with MDD. We included 45 patients with unipolar MDD in a multicentre study. To determine PUFA concentrations, we collected blood samples at the first (T0) and twelfth (T12) ECT-session. We assessed depression severity using the Hamilton Rating Scale for Depression (HAM-D) at T0, T12 and at the end of the ECT-course. ECT-response was defined as 'early response' (at T12), 'late response' (after ECT-course) and 'no' response (after the ECT-course). The PUFA chain length index (CLI), unsaturation index (UI) and peroxidation index (PI) and three individual PUFAs (eicosapentaenoic acid [EPA], docosahexaenoic acid [DHA] and nervonic acid [NA]) were associated with response to ECT using linear mixed models. Results showed a significant higher CLI in 'late responders' compared to 'non responders'. For NA, 'late responders' showed significantly higher concentrations compared to 'early'- and 'non responders'. In conclusion, this study provides the first indication that PUFAs are associated with the efficacy of ECT. This indicates that PUFAs' influence on neuronal electrochemical properties and neurogenesis may affect ECT outcomes. Thereby, PUFAs form a potentially modifiable factor predicting ECT outcomes, that warrants further investigation in other ECT-cohorts.